Penggunaan Media Berbasis Augmented Reality dengan Assemblr Edu untuk Meningkatkan Keterampilan Berpikir Kritis IPAS Kelas V di UPT SDN 060937 Medan Johor - Rambe, Ayu Permata Rizky; Desniarti, Desniarti; Dewi, Ika Sandra; Ayu, Suci Dirma; Sagala, Herbet (Indo-MathEdu Intellectuals Journal, 2025)
The purpose of this research is to improve students' critical thinking skills by using augmented reality (AR) based media with Assemblr Edu application. This research applied the method of classroom action research (PTK) carried out in two cycles, involving 28 grade V students. Techniques applied for data collection were obtained by observation, interviews, and learning outcomes tests. The findings of this study are that the use of AR media provides significant progress in students' critical thinking skills. The percentage of critical thinking skills scores in cycle I was 60%. the percentage increased to 86% in cycle II. The results of the test questions given in cycle I 71% increased in cycle II to 93%. This explains the effectiveness of using AR media in IPAS learning. In conclusion, the use of augmented reality-based media with Assemblr Edu to grade V students at UPT SDN 060937 Medan Johor improves students' critical thinking skills.